PERLINDUNGAN HUKUM KORBAN SALAH TANGKAP OLEH KEPOLISIAN REPUBLIK INDONESIA - Hakim, Lukman; Paidjo, Paidjo; Alamsyah Putra, Tegar Mukmin (Jurnal Hukum Magnum Opus, 2020)
Indonesia is a country of law that upholds justice and guaranteeing all citizens equal before the law in its position without any exceptions. In the opening text of the Constitution of the Republic of Indonesia in 1945 and the first paragraph of the fifth principle of Pancasila prove that Indonesia is a country that upholds the sense of social justice for all Indonesian people, independent country, united, sovereign, just and prosperous. Indonesia received the law as the state ideology to create order, security, justice and prosperity for its citizens. One of the state apparatus that perform the function of the law is the police, one of the actions of the national police is investigating. The process of investigation is the examination process in criminal cases in order to obtain enough information to find and collect evidence on the matter and to find the suspects. Nowadays many cases of wrongful arrests in the investigation process at the police level causing adverse effects on the morale and psychological. How the legal protection for victims of wrongful arrests made by the police of the Republic of Indonesia. The method used in this study is adalahYuridis Normative that is based on the Principles of Law, the rules of law and Regulation Legislation relating to criminal law. In the legal protection as stipulated in the Regulation Legislation that the suspect, defendant or convict is entitled to sue for damages because of being arrested, detained, charged and prosecuted or subjected to other measures, without reason under the Act or in error about the person or the applicable law , Paragraph (2) compensation claim by the suspect or his heirs for the arrest or detention and other measures without reason under the Act or in error about the person or the applicable law as referred to in paragraph (1) that its case was not submitted to the district court, disconnected at a pretrial hearing.Negara Indonesia adalah negara hukum yang menjunjung tinggi rasa keadilan dan menjamin semua warga negara, sama dalam kedudukannya dimata hukum tanpa ada perkecualian. Dalam teks pembukaan Undang Undang Dasar Negara Republik Indonesia 1945 alinea pertama dan Pancasila sila kelima membuktikan bahwa Indonesia adalah negara yang menjunjung tinggi rasa keadilan sosial bagi seluruh rakyat Indonesia, negara yang merdeka, bersatu, berdaulat, adil dan makmur. Indonesia menerima hukum sebagai ideologi negara untuk menciptakan ketertiban, keamanan, keadilan serta kesejahteraan bagi warga negaranya. Salah satu aparatur negara yang menjalankan fungsi hukum adalah Polri, Salah satu tindakan polri adalah penyidikan. Proses penyidikan adalah proses pemeriksaan dalam perkara pidana guna mendapatkan informasi yang cukup, menemukan dan mengumpulkan bukti-bukti mengenai perkara tersebut dan guna menemukan tersangkanya. Sekarang ini banyak kasus salah tangkap dalam proses penyidikan pada tingkat kepolisian menyebabkan kerugian yang berdampak pada moril dan psikis. Bagaimana perlindungan hukum terhadap korban salah tangkap yang dilakukan oleh kepolisian Negara Republik Indonesia. Metode yang digunakan dalam penelitian ini ini adalahYuridis Normatif yaitu berdasarkan Asas-Asas Hukum, kaidah-kaidah hukum dan Peraturan Perundang-Undangan yang berkaitan dengan hukum pidana. Dalam perlindungan hukum sebagaimana diatur di dalam Peraturan Perundang-Undangan bahwa tersangka, terdakwa atau terpidana berhak menuntut ganti kerugian karena ditangkap, ditahan, dituntut dan diadili atau dikenakan tindakan lain, tanpa alasan yang berdasarkan Undang-Undang atau karena kekeliruan mengenai orangnya atau hukum yang diterapkan. Ayat (2) tuntutan ganti kerugian oleh tersangka atau ahli warisnya atas penangkapan atau penahanan serta tindakan lain tanpa alasan yang berdasarkan Undang-Undang atau karena kekeliruan mengenai orang atau hukum yang diterapkan sebagaimana dimaksud dalam ayat (1) yang perkaranya tidak diajukan ke pengadilan negeri,diputus di sidang praperadilan.